Collective Love as Public Freedom: Dancing Resistance. Ehrenreich, Arendt, Kristeva, and Idle No More. (9th December 2016) - Weir, Allison
Abstract : In the Indigenous resistance movement that came to be known as "Idle No More, " round dances played a central role. From the beginning of the movement in western Canada in the winter of 2012–13, and as it spread across Turtle Island (North America) and throughout the world, round dances served to bring together Indigenous and non‐Indigenous activists with people in the streets. "At almost every event, we collectively embodied our diverse and ancient traditions in the round dance by taking the movement to the streets, malls and highways across Turtle Island" (The Kino‐nda‐niimi Collective 2014, 24). But why was the round dance important, and how does the dance work to support political resistance?